2018
DOI: 10.1007/s11105-018-1088-9
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Transcriptomic Analysis Identified Gene Clusters and Candidate Genes for Oil Content in Peanut (Arachis hypogaea L.)

Abstract: Peanut (Arachis hypogaea), a major source of vegetable oil in many Asian countries, has become an integral part of human diet globally due to its high nutritional properties and option to consume in different forms. In order to meet the demand of vegetable oil, many peanut breeding programs of China have intensified their efforts in increasing oil content in newly bred varieties for reducing the import of edible oils in China. In this context, transcriptome sequencing data generated on 49 peanut cultivars were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 42 publications
2
10
0
Order By: Relevance
“…A total of seven QTLs on five LGs were identified in the current study (Table 4). Previous studies have also observed that the trait of oil content was controlled by multiple QTLs, indicating that oil content is polygenetically inherited (Pandey et al 2014;Shasidhar et al 2017;Wang et al 2018a;Wilson et al 2017). According to the physical position of linked markers in the reference genomes of the two diploids, seven QTLs in the present study were mapped to pseudomolecules A04, A05, and A08 in A. duranensis, and to pseudomolecules B05 and B04 in A. ipaensis.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…A total of seven QTLs on five LGs were identified in the current study (Table 4). Previous studies have also observed that the trait of oil content was controlled by multiple QTLs, indicating that oil content is polygenetically inherited (Pandey et al 2014;Shasidhar et al 2017;Wang et al 2018a;Wilson et al 2017). According to the physical position of linked markers in the reference genomes of the two diploids, seven QTLs in the present study were mapped to pseudomolecules A04, A05, and A08 in A. duranensis, and to pseudomolecules B05 and B04 in A. ipaensis.…”
Section: Discussionsupporting
confidence: 59%
“…According to the physical position of flanking markers, annotated information on the putative genes in the QTL interval was downloaded from PeanutBase (https ://www.peanu tbase .org/home). Differentially expressed genes between high-oil cultivars and low-oil cultivars were obtained from Wang et al (2018a).…”
Section: Annotation Of Genes In the Qtl Intervalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The population structure and relative kinship were calculated by the genotype of association panel, and then used in five GWAS statistical methods to control false-positive results. Similar to other studies using peanuts [37,38], the 99 accessions of the Chinese mini-mini core collection in this study were classified into two subgroups (Figure 3). Breeding for peanut varieties for resistance to aflatoxin contamination is the most effective approach for reducing hazards by aflatoxin.…”
Section: Discussionsupporting
confidence: 63%
“…This genetic method has been successfully used to reveal the genetic basis of complex agronomic traits in multiple crops [17][18][19][20]. In peanut, the limited works on association analysis were conducted to evaluate genetic variation in diverse germplasm [21,22].…”
mentioning
confidence: 99%